Comparative transcriptome analysis revealed gene expression differences in fruits between two Actinidia chinensis cultivars - Lina Guo; Kai Yan; Dan Li; Wanxing Li (All Life)
The kiwifruit JD (Jindun No. 1) and HY (Hongyang) are two species of Actinidia chinensis, a major horticultural crop growing worldwide. Fruity texture and taste of HY are better compared with that of JD. However, the fruit transcriptome differences at the ripening stage between JD and HY are poorly understood. In this study, we identified a total of 2,565 differentially expressed genes (DEGs), including 1,336 upregulated and 1,229 downregulated DEGs between the two cultivars. Among the total DEGs, 2,329 matched at least one database. Meanwhile, 1,915 could be aligned to the GO (Gene Ontology), 551 could be aligned to the KEGG (Kyoto Encyclopedia of Genes and Genomes Pathway), and 2,187 could be aligned to SWISS-PROT (SWISS-PROT Protein Sequence) database, respectively. To analyze the DEGs using functional categorization, some regulated processes were significantly changed, and 52 TF (transcription factor) families were detected. This study revealed the change in gene expression level at maturity through the analysis of DEGs data, and these data can provide valuable clues for exploring the molecular mechanism between two kiwifruit varieties, and will be helpful for molecular breeding in Actinidia plants.